Potential Impact of Screening Examinations on Prognosis of De Novo Malignancies in Adult Patients After Liver Transplantation - Sho Uemura; Yasushi Hasegawa; Hideaki Obara; Minoru Kitago; Hiroshi Yagi; Yuta Abe; Shutaro Hori; Masayuki Tanaka; Yutaka Nakano; Yuko Kitagawa (Livers, 2025)
Background: De novo malignancies (DNMs) after liver transplantation (LT) are a major cause of long-term mortality. However, no definitive screening protocol has been established due to their diversity. This study aimed to evaluate DNM diagnosis methods, screening protocols, and prognoses. Methods: This retrospective study included 231 adult LT recipients from April 1997 to March 2021. Disease-specific survival (DSS) was analyzed to assess the impact of screening on prognosis. Most recipients underwent serum tests every three months, annual gastrointestinal endoscopy, and chest-abdominal CT as part of routine surveillance. Results: Twenty-five DNMs were diagnosed in 22 patients, with median age of 61 years (range, 23–72), of whom 13 (59.1%) were female. The duration from transplantation to DNM diagnosis of DNM was 88 months (range, 4–195). DNM was diagnosed as follows: seven patients (31.8%) through screening (screening group) and 15 patients (68.2%) by other means (non-screening group). Curative treatment was achieved in all of the patients diagnosed by screening, whereas it was possible in only 60.0% of patients diagnosed by other means (p = 0.026). DSS in the screening group was significantly longer than that in the non-screening group (p = 0.024). Conclusions: While screening was associated with earlier-stage diagnosis and improved outcomes in some patients, the overall efficacy of the protocol requires further validation in larger studies.